2010
DOI: 10.1186/1757-4749-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of plasmid-mediated quinolone resistance in Salmonella enterica serovar Typhimurium Isolates from Food-Producing Animals in Japan

Abstract: A total of 225 isolates of Salmonella enterica serovar Typhimurium from food-producing animals collected between 2003 and 2007 were examined for the prevalence of plasmid-mediated quinolone resistance (PMQR) determinants, namely qnrA, qnrB, qnrC, qnrD, qnrS, qepA and aac(6')Ib-cr, in Japan. Two isolates (0.8%) of S. Typhimurium DT104 from different dairy cows on a single farm in 2006 and 2007 were found to have qnrS1 on a plasmid of approximately 9.6-kbp. None of the S. Typhimurium isolates had qnrA, qnrB, qnr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…qnrB, qnrS and aac(6¢)-Ib-cr] in this study was similar to previous reports in food animals from Japan (Asai et al, 2010) and humans in France (Cattoir et al, 2007). In contrast, it was higher than previous reports on Vietnamese retail meat and food animals from South Korea (Kim et al, 2011), where no PMQR genes were found.…”
Section: Antimicrobial Resistance In Salmonella In Thailand and Laossupporting
confidence: 88%
See 1 more Smart Citation
“…qnrB, qnrS and aac(6¢)-Ib-cr] in this study was similar to previous reports in food animals from Japan (Asai et al, 2010) and humans in France (Cattoir et al, 2007). In contrast, it was higher than previous reports on Vietnamese retail meat and food animals from South Korea (Kim et al, 2011), where no PMQR genes were found.…”
Section: Antimicrobial Resistance In Salmonella In Thailand and Laossupporting
confidence: 88%
“…Still, provincial slaughterhouses with inadequate hygiene exist and are of particular concern. In contrast, most pigs in Laos are raised on family farms (Boonmar et al, 2008), and small-scale abattoirs with poor hygienic practice in the slaughtering process are still common (Bastiaensen et al, 2011). The samples obtained for this study were collected from a limited number of sites (one slaughterhouse, one fresh market and one hospital in each province), which must be considered when interpreting the data.…”
Section: Discussionmentioning
confidence: 99%
“…By using the broth mating method (8), 9 (3 cattle, 3 swine, and 3 broilers) of 39 (23.0%) isolates were transferred to E. coli DH5␣. All the transconjugants had a size of roughly 60 kb and incompatibility type of IncI2 plasmid by using pulsed-field gel electrophoresis (PFGE) after S1 nuclease digestion (9), a PCR-based replicon-typing assay (10,11), and hybridization (12). These results suggested that they were similar to the plasmid reported by Liu et al in China (1).…”
supporting
confidence: 73%
“…PMQR genes have been detected worldwide in various Enterobacteriaceae (Poirel et al, 2012), and have also been found among Salmonella isolated from human and animal sources in many countries (Gay et al, 2006;Avsaroglu et al, 2007;Cattoir et al, 2007;Hopkins et al, 2007;Cavaco et al, 2009;Cui et al, 2009;Asai et al, 2010). In Korea, PMQR genes were widely reported in human clinical Enterobacteriaceae isolates (Tamang et al, 2008;Kim et al, 2010;Jeong et al, 2011), but have rarely been identified in Enterobateriaceae isolates from animals (Tamang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%